Role Of Fintech In Green Finance And Sustainable Development - Ghosh, Krishnendu (Gyan Management Journal, 2020)
Sustainable development is the common goal of human landscape. The evolution to sustainable economy is an inevitable trend of economic development. FinTech and green finance is strong driving force for sustainable economic development. This article aims to discuss the significant interactions among FinTech, green finance and sustainable development. This paper outlines the broad areas for the possible application of FinTech to green finance and sustainable development. The methodology used for the article is mainly the theoretical framework build based on the existing literature. This study could benefit policymakers and researchers in understanding the implications big data and blockchain and draws preliminary recommendations for policy makers interested in connecting FinTech, big data and blockchain with green finance and sustainable development. The study concludes that FinTech plays a vital role in green finance and sustainable development.